2018
DOI: 10.1007/s00441-018-2817-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors in Parkinson’s disease

Abstract: Over the last two decades, we have witnessed a revolution in the field of Parkinson’s disease (PD) genetics. Great advances have been made in identifying many loci that confer a risk for PD, which has subsequently led to an improved understanding of the molecular pathways involved in disease pathogenesis. Despite this success, it is predicted that only a relatively small proportion of the phenotypic variability has been explained by genetics. Therefore, it is clear that common heritable components of disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
161
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(164 citation statements)
references
References 88 publications
3
161
0
Order By: Relevance
“…However, it is suggested that PD has a complex etiology, involving several molecular pathways, and understanding these specific pathways will be key to establishing mechanistic targets for therapeutic intervention. While several key pathways are currently being investigated, including autophagy, endocytosis, immune response and lysosomal function, [4][5][6][7] mitochondrial function was the first biological process to be associated with PD 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is suggested that PD has a complex etiology, involving several molecular pathways, and understanding these specific pathways will be key to establishing mechanistic targets for therapeutic intervention. While several key pathways are currently being investigated, including autophagy, endocytosis, immune response and lysosomal function, [4][5][6][7] mitochondrial function was the first biological process to be associated with PD 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of PD is complex, including genetic, epigenetic, and environmental factors. Familial PD accounts for less than 10% of the total cases, mostly attributed to monogenic forms with autosomal‐dominant (including SNCA , LRRK2 , and VPS35 ) or autosomal‐recessive pattern of inheritance, such as PARKIN , PINK1 , and DJ‐1 , among others . However, the vast majority of the disease is considered to be sporadic, likely caused by the cumulative effect of multiple common or rare variants of small or moderate effect sizes in addition to other unknown environmental and stochastic factors.…”
mentioning
confidence: 99%
“…The severity of disease correlates with the progressive spread of aggregated αSyn in patients 3 , and αSyn misfolding is associated with toxicity in cell and animal models 4 . In addition, strong genetic evidence links αSyn to PD including gene multiplications or missense mutations that cause rare early onset forms of PD [5][6][7] and genetic association studies also link αSyn to sporadic PD 8,9 . This combined neuropathological, biochemical and genetic evidence provides strong support implicating the misfolding and aggregation of αSyn as a key feature in PD.…”
Section: Introductionmentioning
confidence: 99%